Valuing the conservation of endangered species and their habitats in the Northwest Panay Peninsula Park a preliminary study using contingent valuation method-(Personal Interview) of Kalibo Residents. - Cahilig, Anahaw
Northwest Panay Peninsula (NWPP) is one of the centers of endemism of the country. It is home to diverse species of flora and fauna including species endemic to Panay with status ranging from endangered to critically endangered and an extremely and highly-urgent site for conservation. A survey using Contingent Valuation Method (CVM) was done in selected barangays of kalibo, Aklan to determine the willingness to pay of the residents to the conseration of the enangered species and their habitats in the NWPP. The results showed that the Kalibo-residents were unfamiliar with the existence of the NWPP and the endangered species it harbors. The study yields a mean WTP using the Survivor function Approach of the Kalibo respondents of Php 3.17/ month or Php 38.04/ yearly. Despite the low awareness about the NWPP and the endangered species, the eight barangays included in this would pay Php 283474.08 for its conservation and of all Kalibo residents (Social WTP) with 12,628 households, they would pay Php 480,369.12 annually. With the high level of awareness about NWPP, it is recommended by the researchers that more sources of information should be made available, not just to the Aklanons, but all throughout the country since this abundance in biodiversity are pride of the Filipino Nation.